2009
DOI: 10.1093/cvr/cvp124
|View full text |Cite
|
Sign up to set email alerts
|

Combined reduction of intercellular coupling and membrane excitability differentially affects transverse and longitudinal cardiac conduction

Abstract: Reduction of both electrical coupling and excitability results in normal conduction velocity parallel to fibre orientation but in pronounced conduction slowing transverse to fibre orientation in RV only, although this does not affect arrhythmogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 43 publications
3
52
0
Order By: Relevance
“…We further demonstrate increased sensitivity to G j uncoupling. Therefore, regardless of the mechanism, this study offers a potential explanation for conflicting results concerning the -G j relationship (6,14,18,29,38,41,42,44).…”
Section: Resultsmentioning
confidence: 90%
“…We further demonstrate increased sensitivity to G j uncoupling. Therefore, regardless of the mechanism, this study offers a potential explanation for conflicting results concerning the -G j relationship (6,14,18,29,38,41,42,44).…”
Section: Resultsmentioning
confidence: 90%
“…Second, there was a difference with previous studies using similar mice with a genetically induced 50% reduction in Cx43 expression 16 or a combined 50% reduction in Cx43 and Nav1. 5,32 in which impulse conduction was not (or hardly) disturbed. Interestingly, fibrosis was not found in these mice.…”
Section: Decreased Cx43 Expression Leads To Enhanced Fibrosis and Arrmentioning
confidence: 96%
“…We identified that activation of Tyk2 by Ang II in vitro causes an increase in Cx43 protein level via the STAT3 pathway. Other in vitro examples of an increase in Cx43 protein level include exposing freshly isolated aortas of wildtype mice to Ang II for 4 h and the aorta smooth muscle cell line A7r5 to Ang II from 2 to 48 h (maximum expression was observed at 4 h and was maintained to the last time point of 48 h) (72,73). Conversely, chronic exposure of Ang II in animal models shows a decrease in the protein level of Cx43.…”
Section: Tyk2 Phosphorylates Cx43mentioning
confidence: 99%